2003
DOI: 10.1002/jbm.b.10012
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of parotid saliva proteins and adhesion of Streptococcus mutans ATCC 21752 to dental fiber‐reinforced composites

Abstract: The use of fiber-reinforced composites (FRC) in dentistry has increased during recent years. In marginal areas of crowns and removable partial dentures the fibers may become exposed and come into contact with oral tissues, saliva, and microbes. To date, few articles have been published on oral microbial adhesion to FRCs. The aim of this study was to compare different FRCs, their components, and conventional restorative materials with respect to S. mutans ATCC 21752 adhesion and adsorption of specific S. mutans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 20 publications
2
48
0
1
Order By: Relevance
“…Yet, the composition and ultrastructure of the salivary pellicle also seems to be dependent on the material's chemistry [61,138,140]. Numerous studies suggest that saliva coating generally decreases the bacterial adhesion to teeth and restorative materials [125,[142][143][144][145], although one study found the opposite [146]. In addition, saliva coating reduces the differences in bacterial adhesion to different materials [145,147] and modifies certain properties of the pure material such as surface-free energy and surface charge [118,144].…”
Section: Xxxe11mentioning
confidence: 97%
“…Yet, the composition and ultrastructure of the salivary pellicle also seems to be dependent on the material's chemistry [61,138,140]. Numerous studies suggest that saliva coating generally decreases the bacterial adhesion to teeth and restorative materials [125,[142][143][144][145], although one study found the opposite [146]. In addition, saliva coating reduces the differences in bacterial adhesion to different materials [145,147] and modifies certain properties of the pure material such as surface-free energy and surface charge [118,144].…”
Section: Xxxe11mentioning
confidence: 97%
“…The shortcomings of a rough surface were demonstrated in an in vivo study by Quirynen et al 10 They concluded that the surface roughness of implant-supported prostheses significantly increased the adhesion of supragingival bacterial plaque, increasing the incidence of dental caries, gingivitis, and periodontal disease. [11][12][13][14][15] Finishing and polishing cast titanium are difficult procedures [14][15][16] because of high chemical reactivity, high strength, and low modulus of elasticity. Finishing and polishing affect the mechanical properties of the metal.…”
mentioning
confidence: 99%
“…Many recent studies still use slight rinsing or dipping to remove loosely adhering bacteria, without the realization that all adhering organisms can be regarded as loosely adhering if the rinsing forces applied are sufficiently high (6,10). The literature is therefore fouled with studies confusing the definitions of two terms: adhesion and retention (7).…”
mentioning
confidence: 99%